Rainbow Trout Erythrocytes ex vivo Transfection With a DNA Vaccine Encoding VHSV Glycoprotein G Induces an Antiviral Immune Response - Puente-Marin, Sara; Nombela, Ivan; Chico, Veronica; Ciordia, Sergio; Mena, Maria Carmen; Coll, Julio; Mercado, Luis; Ortega-Villaizan, Maria Del Mar (Frontiers in Immunology, 2018)
Fish red blood cells (RBCs), are integral in several biologic processes relevant to immunity, such as pathogen recognition, pathogen binding and clearance, and production of effector molecules and cytokines. So far, one of the best strategies to control and prevent viral diseases in aquaculture is DNA immunization. DNA vaccines (based on the rhabdoviral glycoprotein G [gpG] gene) have been shown to be effective against fish rhabdoviruses. However more knowledge about the immune response triggered by DNA immunization is necessary to develop novel and more effective strategies. In this study, we investigated the role of fish RBCs in immune responses induced by DNA vaccines. We show for the first time that rainbow trout RBCs express gpG of viral haemorrhagic septicaemia virus (VHSV) (GVHSV) when transfected with the DNA vaccine ex vivo and modulate the expression of immune genes and proteins. Functional network analysis of transcriptome profiling of RBCs expressing GVHSV revealed changes in gene expression related to G-protein coupled receptor (GPCR)-downstream signaling, complement activation, and RAR related orphan receptor α (RORA). Proteomic profile functional network analysis of GVHSV-transfected RBCs revealed proteins involved in the detoxification of reactive oxygen species, interferon-stimulated gene 15 (ISG15) antiviral mechanisms, antigen presentation of exogenous peptides, and the proteasome. Conditioned medium of GVHSV-transfected RBCs conferred antiviral protection and induced ifn1 and mx gene expression in RTG-2 cells infected with VHSV. In summary, rainbow trout nucleated RBCs could be actively participating in the regulation of the fish immune response to GVHSV DNA vaccine, and thus may represent a possible carrier cells for the development of new vaccine approaches.